2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346402
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label classification for the analysis of human motion quality

Abstract: Knowing how well an activity is performed is important for home rehabilitation. We would like to not only know if a motion is being performed correctly, but also in what way the motion is incorrect so that we may provide feedback to the user. This paper describes methods for assessing human motion quality using body-worn tri-axial accelerometers and gyroscopes. We use multi-label classifiers to detect subtle errors in exercise performances of eight individuals with knee osteoarthritis, a degenerative disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…The classification results presented in table III are comparable to this work while having the added benefit of using only one IMU. Taylor and colleagues [16] built on these results in 2012 using a number of different methods to classify human motion quality. Their highest accuracy for the standing hamstring curl was 86% and for the straight leg raise was 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification results presented in table III are comparable to this work while having the added benefit of using only one IMU. Taylor and colleagues [16] built on these results in 2012 using a number of different methods to classify human motion quality. Their highest accuracy for the standing hamstring curl was 86% and for the straight leg raise was 90%.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has also shown that it may be possible to evaluate these exercises more comprehensively [3], [15], [16], and possibly with a single IMU [7], [17]. This study differs from previous work in the field as it aims to evaluate if a single body-worn IMU is capable of distinguishing between seven levels of performance in a compound exercise (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many researchers have developed IMU-based systems to support patients with orthopaedic or musculoskeletal conditions as they perform their rehabilitation exercises at home, providing them with real-time feedback [20][21][22][23][24]. However these platforms have only been evaluated in laboratory based studies.…”
Section: Existing State Of the Artmentioning
confidence: 99%
“…The results of this investigation showed that the 2-week interactive rehabilitation programme was as effective as the conventional rehabilitation programme, thus highlighting the promise for a sensor-based rehabilitation support. However it is worth noting that this system, as well as those referenced in [20][21][22][23][24], used multiple sensors to quantify exercise performance. Using multiple sensors is not convenient for patients to set-up and use in the home.…”
Section: Existing State Of the Artmentioning
confidence: 99%